2022
DOI: 10.2138/am-2022-8109
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally derived F, Cl, and Br fluid/melt partitioning of intermediate to silicic melts in shallow magmatic systems

Abstract: The conditions under which halogens partition in favour of an exsolved fluid relative to the coexisting melt are key for understanding many magmatic processes, including volcanic degassing, evolution of crustal melt bodies, and ore formation. We report new F, Cl and Br fluid/melt partition coefficients for intermediate to silicic melts, for which F and Br data are particularly lacking; and for varying CO 2 -H 2 O contents to assess the effects of changing fluid composition (XH 2 O) on Br fluid/melt partitionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 88 publications
(113 reference statements)
3
3
0
Order By: Relevance
“…In contrast, SO 2 /HF was very high over the lava field, suggesting that HF does not behave in a similar fashion to HCl under the conditions at Holuhraun and was not significantly degassing in the flows syn-eruption—this is consistent with other measurements made of gas around the eruption site that likely reflect a combination of the main plume and the lava field emissions (Gíslason et al 2015 ; Ilyinskaya et al 2017 ; Stefánsson et al 2017 ), and with the HCl/HF ratios. It is also consistent with recent work on F partitioning (Cassidy et al 2022 ). These results are in contrast to the filter pack measurements report in Sigmarsson et al( 2020 ) who found that SO 2 /HF was much lower (two orders of magnitude) in the residual gas from the lava field (after the eruption finished) than during the eruption.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In contrast, SO 2 /HF was very high over the lava field, suggesting that HF does not behave in a similar fashion to HCl under the conditions at Holuhraun and was not significantly degassing in the flows syn-eruption—this is consistent with other measurements made of gas around the eruption site that likely reflect a combination of the main plume and the lava field emissions (Gíslason et al 2015 ; Ilyinskaya et al 2017 ; Stefánsson et al 2017 ), and with the HCl/HF ratios. It is also consistent with recent work on F partitioning (Cassidy et al 2022 ). These results are in contrast to the filter pack measurements report in Sigmarsson et al( 2020 ) who found that SO 2 /HF was much lower (two orders of magnitude) in the residual gas from the lava field (after the eruption finished) than during the eruption.…”
Section: Discussionsupporting
confidence: 93%
“…Their model suggests that such systems should move from an initially S-rich melt and gas towards a relatively Cl–Br rich melt and gas, as is also suggested by our data, particularly from Fimmvörðuháls. Furthermore, recent studies suggest that Cl solubility in the melt is strongly dependent on temperature, with decreasing temperature in mafic systems leading to decreasing Cl solubility (Cassidy et al 2022 ; Thomas and Wood 2021 ), consistent with some HCl degassing from the flows. Cassidy et al ( 2022 ) further note that the partitioning of halogen species is strongly compositionally dependent, with their experimental measurements of D Br f/m ranging from 7.1 + / − 6.4 in basaltic andesite to 31.3 + / − 20.9 in dacite.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Instead, the compositional trend of our apatite inclusions closely matches those of the H2O-saturated crystallisation models (Fig. 7g), where Cl is partitioned from the melt into an exsolving vapour phase while F is retained in the felsic melt (Candela, 1986;Cassidy et al, 2022;Doherty et al, 2014;Stock et al, 2018;Webster et al, 2009). As the solubility of H2O in a magmatic system is mainly pressure-dependent, the trajectory of apatite volatile evolution should be different during isobaric and polybaric (decompressed) H2O-saturated crystallisation.…”
Section: 𝐷 /supporting
confidence: 66%
“…has been shown to be <0.1 (Webster and Holloway 1990), and more recent experiments show that D fluid−melt F(i) is generally <1 in felsic magma systems (Cassidy et al 2021).…”
Section: Modelling Melt Volatile Evolution Under Fluid-saturated and ...mentioning
confidence: 96%